Risk factor analysis of baby blues symptomsin postpartum women with a history of complications during childbirth - Sormin, Roslin EM; Atok, Yosefa Sarlince; Manek, Brigita Dina; Palalangan, Damita; Babis, Isna Yuswella (Alma Ata University Press, 2025)
Background: Postpartum emotional mental disorders, one of which is postpartum blues or known as baby blues. If during pregnancy and child birth the mother experiences complications, this can exacerbate her emotional changes. Objectives: This study aims to analyze the risk factors for the occurrence of baby blues symptoms in postpartum women with a history of complications during childbirth.Methods: This type of research is descriptive analytic, using across sectional approach. Sampling was carried out by accidental sampling method where the sample and sample size were taken based on the time limit for data collection, namely mothers who visited the postpartum period 1-14 days at SK Lerik Kupang Hospital, NTT in April-June 2023. Dataon patient characteristics were taken using a questionnaire, while measuring the diagnosis ofbaby bluesusing the PASS (Perinatal Anxiety Screening Scale) questionnaire. Results: Data analysis used was univariate analysis with frequency distribution table, bivariate analysis with simplelogistic regression, multivariate analysis with multiple logistic regression. The results of this study indicate that more than half (68%) of postpartum mothers with a history of complications during childbirth (68%) have a high risk of experiencing postpartum blues. Factors that can influence the occurrence ofpostpartum bluesin mothers with a history of complications during child birth are the type of delivery (p=0.001), mother's occupation (p=0.004), family income(p=0.011), husband's support (p = 0.000), and social support (p=0.005).Conclusions: Factors that can increase the risk of baby blues syndrome in mothers with a history of child birth complications are mothers who under go cesarean section, housewives, mothers whose household income is lessthan the Regional Minimum Wage (UMR),and mothers who do not get support fromtheir husbands, and do not receive social support from family, neighbors and friends and the surrounding community.